Amplitude ratios and the approach to bulk criticality in parallel plate geometries - Leite, M. M. [UNESP]; Sardelich, M.; Coutinho-Filho, M. D. (American Physical Society (APS), 1999)
We present analytical and numerical results for the specific heat and susceptibility amplitude ratios in parallel plate geometries. The results are derived using field-theoretic techniques suitable to describe the system in the bulk limit, i.e., (L/ξ±)≫ 1, where L is the distance between the plates and ξ± is the correlation length above (+) and below (-) the bulk critical temperature. Advantages and drawbacks of our method are discussed in the light of other approaches previously reported in the literature.